FREEDOM OF CONTRACT AND STATE INTERVENTION IN INDONESIA AND SUDAN: FOREIGN INVESTMENT LAW PERSPECTIVE - Pradnya Radjani, Ni Wayan Julia; Agus Kurniawan, I Gede; Fathi Aboalela, Nahi Hashim (Kanun Jurnal Ilmu Hukum, 2025)
This study examines the relationship between freedom of contract and state intervention within the framework of foreign investment law in Indonesia and Sudan, focusing on how both countries balance legal certainty for investors with the protection of national interests. Employing a normative legal research method with comparative and conceptual approaches, this study analyzes primary legal sources, i.e. the 1945 Constitution of Indonesia, Sudans Investment Promotion Act (2021), and relevant investment regulations, alongside secondary sources including academic literature and economic policy documents. The findings reveal that Indonesia adopts a regulated freedom model, where the principle of contractual autonomy is recognized insofar as it aligns with the constitutional mandate of Article 33 of the 1945 Constitution through the doctrine of State Control Rights (Hak Menguasai Negara, HMN). State intervention is implemented under the Right to Regulate framework, particularly through strategic sector restrictions and the industrial downstreaming (hilirisasi) policy designed to ensure domestic value creation. Conversely, Sudan applies a value-based freedom model rooted in Islamic law, in which contractual freedom is constrained by the principles of Hisbah and prohibitions against riba (usury), gharar (uncertainty), and maysir (speculation). The legitimacy of Sudans intervention also derives from post-conflict reconstruction needs and the imperative to safeguard economic stability. The comparative analysis demonstrates that although their philosophical foundations differ, both countries reject the notion of absolute contractual freedom and reaffirm that state sovereignty remains a fundamental element in their investment law regimes. This research emphasizes the importance of a socially responsible freedom model as a convergence point between national investment law and the evolving global economic legal order.